Działalność kodyfikacyjna Romualda Hubego - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Romuald Hube was one of the most prominent Polish legal historians of the 19th century. He was also a very active jurist who was a member of several governing authorities in the Kingdom of Poland. As a very distinguished lawyer, characterized by a loyalistic attitude towards the government of the Kingdom of Poland, he was appointed to a Commission whose goal was to codify Russian law and unify with it the law in force in the Kingdom of Poland. The most significant of these codifications the result of Romuald Hube’s work was the Code of Principal and Corrective Penalties issued for Russia in 1845, and in 1847 for Poland. The introduction of this Code, which was very critically received by the Polish society, brought down a wave of criticism on Romuald Hube, related not only to the legal solutions adopted in this Code itself, but above all to the role he played in the repressive policies of the Russian authorities against the Polish population. Romuald Hube’s participation in the creation of the Code still raises many controversies in Polish academic circles.
Keywords: Code of Principal and Corrective Penalties; codification of law; the Codification Commission; Kingdom of Poland; Hube, Romuald (1803–1890)